The Impact of Chronic Hypertension, Kidney Disorders, and Employment Status on Preeclampsia in Makassar - Iskandar, Imelda; Syam, Azniah; Fitrianingtyas, Dwi Elineng; Tajriani, Tajriani (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Preeclampsia is a serious pregnancy complication characterized by hypertension and organ dysfunction, especially the kidneys, which usually appear after 20 weeks of gestation. In Indonesia, preeclampsia is one of the leading causes of maternal and fetal morbidity and mortality. The high maternal mortality rate in this country requires a deeper understanding of the risk factors for preeclampsia in order to formulate more effective and targeted prevention strategies. This study aims to identify the main risk factors for preeclampsia in pregnant women in the Pampang Health Center working area, Makassar City, and to evaluate the influence of these factors on the incidence of preeclampsia. This study used a cross-sectional design involving 200 pregnant women, consisting of 100 women with preeclampsia and 100 without preeclampsia. Taken systematically from medical records for the period 2021 – 2023. Data were collected from medical records and confirmed through interviews if necessary. Data analysis used the Chi-square test with p <0.05. The main findings show that a history of preeclampsia, chronic hypertension, renal impairment, autoimmune conditions, and maternal employment status are significant risk factors for preeclampsia. Working mothers with chronic hypertension had a higher risk of preeclampsia (81.8%) compared to non-working mothers (30.1%). This study highlights the importance of intensive monitoring for mothers with high-risk factors. Working mothers are more susceptible to stress and hypertension, increasing the risk of preeclampsia. A history of autoimmune and renal impairment also shows a strong association with preeclampsia. History of preeclampsia, chronic hypertension, renal impairment, autoimmune conditions, and maternal employment status are significant risk factors for preeclampsia. Recommendations include intensive monitoring, education and support for pregnant women, especially those who work, and further longitudinal studies for a clearer causal relationship. Objective medical validation is needed for subjective variables to improve data accuracy.